Does premature elevated progesterone on the day of trigger increase spontaneous abortion rates in fresh and subsequent frozen embryo transfers?. (3rd June 2017) - Healy, Mae; Patounakis, George; Zanelotti, Austin; Devine, Kate; DeCherney, Alan; Levy, Michael; Hill, Micah J.
Abstract: Recent evidence has shown elevated progesterone ( P ) advances the endometrium in fresh ART cycles, creating asynchrony with the embryo and thus implantation failure and decreased live birth rates. If the window of implantation is closing as the embryo attempts to implant, there may be difficulty with trophoblastic invasion, leading to failure of early pregnancies. Our objective was to evaluate if P on the day of trigger was associated with spontaneous abortion (SAB) rates in fresh ART transfers. This was a retrospective cohort study involving fresh autologous and FET cycles from 2011 to 2013. The main outcome was spontaneous abortion rates. About 4123 fresh and FET transfer cycles were included which resulted in 1547 fresh and 491 FET pregnancies. The overall SAB rate was 20% among fresh cycles and 19% in FET cycles. P on the day of trigger, as a continuous variable or when > 2 ng/mL, was not associated with SAB in fresh cycles. Similar results were found after adjusting for age, embryo quality, and embryo stage. Despite elevated P likely advancing the window of implantation, once implantation occurs, pregnancies were no longer negatively impacted by progesterone.